2021
DOI: 10.3390/en14051352
|View full text |Cite
|
Sign up to set email alerts
|

A CFD Study on Flow Control of Ammonia Injection for Denitrification Processes of SCR Systems in Coal-Fired Power Plants

Abstract: The selective catalytic reduction method is a useful method for the denitrification process of exhaust gas emitted from industrial facilities. The distribution of the ammonia–nitrogen oxide mixing ratio at the inlet of the catalyst layers is important in the denitrification process. In this study, a computational analysis technique was used to improve the uniformity of the NH3/NO molar ratio by controlling the flow rate of the ammonia injection nozzle according to the flow distribution of nitrogen oxides in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…1−3 Selective catalytic reduction (SCR) denitration systems are widely used in power plants to treat NO x . 4,5 Catalysts are the key to SCR denitration technology. 6 Controlling the deactivation rate of the catalyst is of great significance for the long period stable operation of the SCR denitration system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1−3 Selective catalytic reduction (SCR) denitration systems are widely used in power plants to treat NO x . 4,5 Catalysts are the key to SCR denitration technology. 6 Controlling the deactivation rate of the catalyst is of great significance for the long period stable operation of the SCR denitration system.…”
Section: Introductionmentioning
confidence: 99%
“…Coal combustion for thermal power generation is the most conventional way to use coal. Coal combustion will produce a large number of pollutants, such as gaseous NO x and fly ash. Selective catalytic reduction (SCR) denitration systems are widely used in power plants to treat NO x . , Catalysts are the key to SCR denitration technology . Controlling the deactivation rate of the catalyst is of great significance for the long period stable operation of the SCR denitration system .…”
Section: Introductionmentioning
confidence: 99%
“…The combustion of fossil fuels, especially in coal-fired power plants, is one of the main sources of x NO in the atmosphere [1]- [3]. Currently, thermal power plants have two ways to reduce x NO emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Sohn et al also suggested placing the AIG and mixer away from the catalyst layer to enhance the NH 3 mixing and flow uniformity together [17]. Moreover, Kim et al used a computational analysis technique to improve the uniformity of the NH 3 /NO molar ratio by controlling the flow rate of the ammonia injection nozzle according to the flow distribution of the nitrogen oxides in the inlet exhaust gas of the denitrification facility [18]. Based on the response surface methodology (RSM), Ye et al studied the effect of three factors on denitration efficiency, including catalyst inlet gas velocity, reaction temperature, and the NH 3 /NO molar ratio.…”
Section: Introductionmentioning
confidence: 99%